Новый вид рода Apanteles Foerster группы merula (Hymenoptera, Braconidae) из Черноморского заповедника - Котенко, А.Г. (Вестник зоологии, 1981)
The paper deals with the description of Apanteles meratus sp. n., new for science species from the Black Sea reservation (South of the Ukraine). It differs from A. myeloenta W i l k i n s o n in the head shape, a more glittering face and mesoscutum, an almost smooth propodeum and a shorter metacarp. The holotype and three paratypes are preserved at the Institute of Zoology of the Ukr. SSR Academy of Sciences (Kiev), I paratype — at the Zoological Institute of the USSR Academy of Sciences (Leningrad). A key of the merula group species known from Europe is presented.